Application of Reaction Force Field Molecular Dynamics in Lithium Batteries - Shi, Zhihao; Zhou, Jian; Li, Runjie (Frontiers in Chemistry, 2021)
Lithium batteries are widely used in portable electronic products. Although the performance of the batteries has been greatly improved in the past few decades, limited understanding of working mechanisms at atomic scale becomes a major factor for further improvement. In the past ten years, a reaction force field (ReaxFF) has been developed within molecular dynamics framework. The ReaxFF is demonstrated to correctly describe both physical processes and chemical reactions for a system significantly larger than the one simulated by quantum chemistry, and therefore turns to be broadly applied in lithium batteries. In this article, we review the ReaxFF studies on sulfur cathode, various anodes and electrolytes of lithium batteries and put particular focus on the ability of the ReaxFF for revealing atomic-scale working mechanisms. A brief prospect is also given.